Interactive Effects of Ocean Acidification and Nitrogen-Limitation on the Diatom Phaeodactylum tricornutum - Li, Wei; Gao, Kunshan; Beardall, John; 高坤山 (PLOS ONE, 2012)
National Basic Research Program of China [2009CB421207, 2011CB200902]; National Natural Science Foundation [40930846, 41120164007]; Program for Changjiang Scholars and Innovative Research Team [IRT0941]; China-Japan collaboration project from MOST [S2012GR0290] Climate change is expected to bring about alterations in the marine physical and chemical environment that will induce changes in the concentration of dissolved CO2 and in nutrient availability. These in turn are expected to affect the physiological performance of phytoplankton. In order to learn how phytoplankton respond to the predicted scenario of increased CO2 and decreased nitrogen in the surface mixed layer, we investigated the diatom Phaeodactylum tricornutum as a model organism. The cells were cultured in both low CO2 (390 mu atm) and high CO2 (1000 mu atm) conditions at limiting (10 mu mol L-1) or enriched (110 mu mol L-1) nitrate concentrations. Our study shows that nitrogen limitation resulted in significant decreases in cell size, pigmentation, growth rate and effective quantum yield of Phaeodactylum tricornutum, but these parameters were not affected by enhanced dissolved CO2 and lowered pH. However, increased CO2 concentration induced higher rETR(max) and higher dark respiration rates and decreased the CO2 or dissolved inorganic carbon (DIC) affinity for electron transfer (shown by higher values for K-1/2 DIC or K-1/2 CO2). Furthermore, the elemental stoichiometry (carbon to nitrogen ratio) was raised under high CO2 conditions in both nitrogen limited and nitrogen replete conditions, with the ratio in the high CO2 and low nitrate grown cells being higher by 45% compared to that in the low CO2 and nitrate replete grown ones. Our results suggest that while nitrogen limitation had a greater effect than ocean acidification, the combined effects of both factors could act synergistically to affect marine diatoms and related biogeochemical cycles in future oceans.